(untitled) (De la Crítica, 2025)
Venezuelan dramaturgy has undergone a remarkable transformation and evolution over time, clearly reflecting the postmodernist influence that has shaped contemporary theater by addressing topics that challenge a society rooted in rigid traditions. La máxima felicidad, written by Isaac Chocrón, alludes to the volatility and divergence of human relationships, exploring concerns about the way the family unit has evolved over time. Additionally, the play presents the possibility of a family bond that, despite its contradictions and conflicts, achieves harmonious coexistence and emotional balance. For this critical approach, we have drawn upon the theories of Rojas (1986) and Azparren (1997), whose research has focused on the history and critique of Venezuelan theater and dramaturgy in the country. It can be concluded that this play provides clear evidence of the lyrical richness found in Venezuelan dramaturgy, as it not only presents a controversial and compelling story but also invites readers to reflect. It conveys the idea that "ultimate happiness" is not necessarily aligned with society’s imposed standards but rather emerges from the blend of experiences and traditions of a group of people who, despite lacking blood ties, manage to establish a meaningful balance based on mutual tolerance and respect for differences. Keywords: Happiness, Dramaturgy, Theater.